Association of Blood Pressure and Risk of Cardiovascular and Chronic Kidney Disease in Hong Kong Hypertensive Patients. Issue 2 (August 2019) - Wan, Eric Yuk Fai; Yu, Esther Yee Tak; Chin, Weng Yee; Fong, Daniel Yee Tak; Choi, Edmond Pui Hang; Lam, Cindy Lo Kuen
Abstract : The association between systolic blood pressure, cardiovascular disease, and chronic kidney disease remains unclear. This study aimed to evaluate these relationships. A population-based cohort of 267 469 adult patients with hypertension but without diabetes mellitus, cardiovascular disease, or chronic kidney disease were identified. Using baseline and repeated systolic blood pressure (average of all systolic blood pressure measurements in the past 5 years), the risks of cardiovascular disease and chronic kidney disease associated with systolic blood pressure were evaluated by Cox regression. Subgroup analyses were conducted by baseline characteristics. Over 1.4 million person-years follow-up (median 6 years), 29 500 cardiovascular disease and 30 993 chronic kidney disease events diagnosed. A J-shape association between baseline systolic blood pressure and risks of cardiovascular disease and chronic kidney disease was observed. Using repeated systolic blood pressure, a positive and log-linear association was identified. There was no evidence of a threshold down to the repeated systolic blood pressure of 120 mm Hg. Increases of 10 mm Hg of repeated systolic blood pressure was associated with a 16% (hazard ratio, 1.15; [95% CI, 1.13–1.16]), 11% (1.11; [1.08–1.13]), and 22% (1.22; [1.20–1.24]) higher risk of composite of cardiovascular disease and chronic kidney disease, individual cardiovascular disease and chronic kidney disease, respectively. Strength of the associations was similar across different subpopulations. This study showed that hypertensive patients with elevated repeated systolic blood pressure are at increased risk of cardiovascular disease or chronic kidney disease, irrespective of different characteristics. Very low single measurement of systolic blood pressure may be a potential indicator for poor health, but there seems to be no threshold for usual systolic blood pressure. Abstract : Supplemental Digital Content is available in the text.